Physical Activity and Gallstone Disease - I. N. Grigor’eva; T. E. Notova; T. I. Romanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to present data of Russian and foreign studies about association between physical activity (PA) and gallstone disease (GSD).Key point. A low PA level is one of the four major risk factors for chronic non-infectiuos diseases. The frequency of low PA in men and women of the Russian Federation (according to the medical examination in 2016) is 19 %. The global prevalence of GSD is up to 20 % among adults. Many systematic reviews and meta-analyses have confirmed an inverse association between GSD and PA in the world, regardless of potential risk factors for GSD, with a clear dose-dependent effect — the relative risk (RR) of GSD was 0.87 (95 % CI 0.83–0.92) per 20 metabolic equivalents (MET) of PA per week. According to our results of an epidemiological survey in the framework of the WHO MONICA program in Novosibirsk (n = 870) among women aged 25–64 with low total PA (less than 800 MET/min/week), as well as with the first class of PA in leisure-time, GSD occurred much more often (class 1 — 33 %, classes 2–4 — 8.7–11.0 %, p < 0.01). PA favorably affects almost all mechanisms of gallstone formation: improves cholesterol metabolism in bile, increases serum HDL cholesterol, bile acid synthesis, stimulates the release of cholecystokinin, reduces mucin hypersecretion, increases the diversity and richness of the intestinal microbiota. Daily PA serves as a preventive measure for GSD: the risk of GSD is reduced by 66 % (95 % CI 0.18–0.86).Conclusion. EASL has recognized PA as a protective agent against gallstone formation.